Effect of Population Density on Sex Ratio in North Sumatera Province - Rahma Dhea Safitri; Rizky Nurhasanah; Regita Audyna Siregar; Victor Asido Elyakim P; Yuegilion Pranayama Purba (JOMLAI: Journal of Machine Learning and Artificial Intelligence, 2025)
This study evaluates the effect of population density on the sex ratio in North Sumatra Province based on 2025 data. This study collected data on population size, land area, and sex ratio from each district and city in the province. Population density was calculated as the result of dividing the population by the land area, then its relationship with the distribution of male and female ratios in each region was analyzed. Data were quantitatively analyzed using statistical correlation approaches, such as Pearson correlation and simple linear regression, to identify potential relationships between density levels and sex ratio differences. The research results indicate that the relationship between population density and the sex ratio in North Sumatra Province is very weak and not statistically significant. The Pearson correlation coefficient value of -0.114 and the coefficient of determination (R²) of 0.013 show that only about 1.3% of the variation in the sex ratio can be explained by population density. These findings indicate that other factors, such as age composition, selective migration, economic structure, as well as socio-cultural factors and local policies, are more dominant in shaping the sex ratio between regions. Nevertheless, these findings provide initial insights into the social dynamics of the population as a basis for more comprehensive regional planning and demography-based development policies.